Effectiveness of neoadjuvant chemotherapy with cisplatin and irinotecan followed by surgery on small-cell carcinoma of the esophagus: A case report. (2015) - Akiyama, Yuji; Iwaya, Takeshi; Shioi, Yoshihiro; Endo, Fumitaka; Chiba, Takehiro; Otsuka, Koki; Nitta, Hiroyuki; Koeda, Keisuke; Mizuno, Masaru; Uesugi, Noriyuki; Kimura, Yusuke; Sasaki, Akira
Highlights: Small-cell carcinoma of the esophagus is a rare disease and a poor prognosis. The optimum treatment strategy for SCCE remains to be established. We report a case of advanced SCCE achieving a pathologically complete response with preoperative chemotherapy using CDDP and CPT-11, and long-term survival followed by surgery. Neoadjuvant chemotherapy following esophagectomy could be a useful treatment option. Abstract: Introduction: Small-cell carcinoma of the esophagus (SCCE) is a rare disease with aggressive progression and a poor prognosis. A standard treatment strategy for SCCE is yet to be established. Presentation of case: A 40-year-old woman with dysphagia was admitted to our hospital. A clinical diagnosis of SCCE (T3N1N0 stage IIIA) was established. She was initially treated with chemotherapy using cisplatin (CDDP) and irinotecan (CPT-11). After two courses of treatment, the primary lesion in the esophagus was not detectable by esophageal endoscopy. Likewise, swelling of the right recurrent nerve lymph node present prior to treatment could not be detected. The chemotherapy resulted in a complete response. One month after the conclusion of chemotherapy, radical esophagectomy with three-field lymph node dissection was performed. Histopathological examination of the excised specimen revealed no residual tumor or lymph node metastasis. The patient was discharged from hospital 29 days after surgery with no complications. The patient is alive and has remained cancer-free for 48 months after the surgery. Discussion: Systemic chemotherapy for SCCE in combination with surgery was treated after surgery in most reports. Neoadjuvant chemotherapy is advantageous from three viewpoints, namely achievement of downstaging, increasing complete resection rates, and a better completion of treatment compared with postoperative chemotherapy. Neoadjuvant chemotherapy following esophagectomy could be a useful treatment option for patients with limited disease (LD) of SCCE. Conclusion: We report a case of SCCE achieving a pathologically complete response with neoadjuvant chemotherapy using CDDP and CPT-11, and long-term survival followed by surgery.